Agrobacterium tumerfaciens mediated transformation and regeneration of Cucumis melo plants - WANG Hui-zhong; LI Ya-nan; ZHAO Pei-jie (浙江大学学报. 农业与生命科学版)
Segments of cotyledonary explants can be infected by Agrobacterium tumefaciens harboring a binary vector pBEWMV. Fertile transgenic plants were obtained. The results of NPT-Ⅱ enzyme activity assay, DNA dot hybridization and Southern blot analysis indicated that npt-Ⅱ gene and WMV-1 CP gene had been integrated into the genome of Cucumis melo.